La relación entre las Prácticas ESG y el Riesgo Idiosincrático: Evidencia desde la Alianza del Pacífico - Huamán Ticlavilca, Rafael Cristian (2024)
This thesis analyzes the relationship between performance in Environmental, Social, and Governance (ESG) factors and idiosyncratic risk in companies from the Pacific Alliance countries, using data from 2016 to 2022. The study applies econometric models, incorporating control variables such as company size, leverage and market-to-book ratio. Furthermore, it distinguishes the effect based on company size and sector sensitivity among others. The findings reveal that higher ESG scores significantly correlate with reductions in idiosyncratic risk, highlighting the effectiveness of ESG practices in mitigating unsystematic risk. These results underscore the importance of integrating ESG practices into risk management improvement and provide valuable insights for investors and entrepreneurs.